Lifting Kit for Flooded Furnitures: Mechanical Design and Strength Analysis - Muhammad Dzulkifly; Raffy Frandito; Mochammad Rafli Ramadhani; Wildan Rahmawan; Farid Triawan (Journal of Mechanical Engineering and Mechatronics, 2021)
Almost every year, floods disaster becomes the scourge of many countries in the world, including Indonesia.  When the flood comes and submerges the houses, every item and household furniture in it will also be submerged in flood water. Furniture that is heavy and difficult to move, especially electronic equipment such as refrigerators, may be left by the owner when a flood occurs. To prevent the furniture from submerging, a lifting kit is needed. For this reason, the purpose of this work is to design a mechanical tool/kit that can lift or elevate the electronic furniture such as refrigerator to a higher position and avoid the damage caused by flood. The kit is expected to be able to cover a 100 x 80 cm base of the refrigerator with maximum load of 200 kg. The elevation of the lifting kit is set to be higher than 50 cm. Calculation for the stress and fatigue analysis is also performed to determine the strength of the structure. As a result, the obtained safety factors for the critical components under static and fatigue loading conditions show values of more than one, indicating the product is safe for real operation. In addition, the required torque to produce the elevation is also calculated and discussed.